Worldwide Destinations Casebook : The geography of travel and tourism - Boniface, Brian G.; Cooper, Chris, 1952- (Amsterdam ; Oxford : Butterworth-Heinemann, 2009)
'Worldwide Destinations Casebook' provides over 40 comprehensive case studies of international tourism destinations. A companion text to the core textbook 'Worldwide Destinations', these cases contextualise the learning and provide real life illustrations of the theories covered.
Previous ed.: Amsterdam; London: Elsevier Butterworth-Heinemann, 2005.
Includes bibliographical references and index.
Keywords: Tourism; Travel